Analysis of the Possibility of Adapting Basement Premises in Multi-Story Buildings as Civil Protection Shelters - Yurchenko, Ihor (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article examines the possibility of adapting basement premises in multi-story buildings in light of state building code requirements. Based on drawings, the author conducted an analysis of key structural parameters such as entrance width, ceiling height, area, and their compliance with regulatory requirements. The study aims to evaluate the effectiveness of using basement premises as shelters in the context of modern civil protection challenges. The analysis results can be used to improve regulatory documentation and adapt existing basement premises for civil protection needs.
Keywords: basements of multi-story buildings; civil protection shelters; civil protection